Kajian Pengemasan yang Berbeda Wadi Ikan Jelawat (Leptobarbus hoevenii) dengan Formula Campuran Media Beras dan Wijen - Petrus Petrus; Tyas Wara Sulistyaningrum; Evnaweri Evnaweri (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2021)
Fermented Mad Barb (Leptobarbus hoevenii) fish with mixed media of rice and sesame is an innovative product with added value. The better the packaging of the fermented mad barb fish will extend the shelf life of it. The aim of this research was to determine the best packaging which based on the growth of the bacterial colonies and the level of consumer acceptance of fermented mad barb fish which has been stored for 30 days at the room temperature. This research used Complete Randomized Design (CRD) with 3 different treatments and 3 repetitions or tests. The treatment in this research was using standing pouch, aluminum foil, and polypropylene (PP) plastic to package the fermented mad barb fish. In this research, the fermented mad barb fish products were stored for 30 days in room temperature then TPC and organoleptic testing were carried out after, where the samples were tested and observed on day 0, day 15, and day 30. The result of this research showed that the packaging of fermented mad barb fish using PP plastic with vacuum technique had good results. It can be seen from the result of the TPC test with the total number of bacterial colonies on the 30th day was the lowest among the others. In organoleptic test also showed that the packaging of fermented mad barb fish showed better results than other packaging in terms of aroma, taste, texture and color. Keyword : Fermented, Mad Barb Fish, packaging